Answer:
A) x² + 7x - 9
Step-by-step explanation:
Deduct\Add each like-term to arrive at your answer.
A single, six-sided die is rolled. Find the probability of rolling an even
number or a number less than 3
Answer:
5/6 (if including 3) 4/6 (not including 3)
Step-by-step explanation:
1 and 2 are less than 3
4 and 6 are even
that leaves 5 and 3.
so 4 of the numbers are even or less than 3
Probability of rolling even number or number less than 3 is 2/3.
What is probability?Probability is defined by the possibility of the event to happen which is ratio of no. of favorable outcomes and the total no. of outcomes.
Probability of event = P(E) = No. of favorable outcomes/Total No. of outcomes
Here given that the dice is fair and six-sided is rolled.
Total no. of outcomes by rolling the dice=6 i.e. {1,2,3,4,5,6}
No. of favorable outcomes of getting even no. =3 i.e. {2,4,6)
Probability of rolling an even no.=P(even)= No. of favorable outcomes/Total No. of outcomes = 3/6
No. of favorable outcomes of getting no. less than 3 =2 i.e. {1,2}
Probability of rolling no. less than 3=P(<3) =No. of favorable outcomes/Total No. of outcomes = 2/6
No. of favorable outcomes of getting even no and number less than 3 =1 i.e. {2}
Probability of rolling an even no. and no. less than 3 =P(even and <3) = P(even ∩ <3)= No. of favorable outcomes/Total No. of outcomes = 1/6
As we know P(A∪B)=P(A)+P(B)-P(A∩B)
Probability of rolling an even no.or no. less than 3 = P(even or <3) = P(even ∪ <3)= P(even)+P(<3)-P(even ∩ <3)
=(3/6)+(2/6)-(1/6)
=4/6
=2/3
Therefore probability of rolling even number or number less than 3 is 2/3.
Learn more about probability
here: https://brainly.com/question/14192140
#SPJ2
(1/x)+(1/x-y)
Please solve this question. I will mark you brainliest.
Answer:
[tex]\frac{2x-y}{x(x-y)}[/tex]
Step-by-step explanation:
To express as a single fraction
multiply numerator/denominator of [tex]\frac{1}{x}[/tex] by (x - y) and
multiply numerator/ denominator of [tex]\frac{1}{x=y}[/tex] by x
= [tex]\frac{x-y}{x(x-y)}[/tex] + [tex]\frac{x}{x(x-y)}[/tex]
Add the numerators leaving the denominator
= [tex]\frac{2x-y}{x(x-y)}[/tex]
What is the solution
Answer:
y ≥ 14.
Step-by-step explanation:
y - 27 ≥ -13 Add 27 to both sides:
y ≥ 14 (answer).
For this case we must find the solution of the following inequality:
[tex]y-27 \geq-13[/tex]
We must add 27 to both sides of the inequality:
[tex]y \geq-13 + 27[/tex]
We know that different signs are subtracted and the sign of the major is placed.[tex]y \geq14[/tex]
So, the solution is [tex]y \geq14[/tex]
Answer:
Option C
05.07) The net of a pyramid is shown below: The net of a square based pyramid, with bases labeled 7 inches and the height of the triangle labeled 14 inches. The surface area of the solid is ____ square inches. Numerical Answers Expected!
Answer: 245 [tex]in^{2}[/tex]
Step-by-step explanation:
You can find the Surface Area of a figure by adding up the areas of each shape.
First you have to find the area of the base.
7×7 = 49
Then you can find the area of the 4 triangles that complete the pyramid.
Formula for area of a triangle: [tex]\frac{1}{2} bh[/tex] (one half of base times height)
[tex]\frac{1}{2} (14*7) = x\\\frac{1}{2} 98 = x\\x = 49[/tex]
Since all the triangles are the same, you only have to calculate that once.
Now you just add everything together, and that's your surface area.
[tex]49+49+49+49+49= 245[/tex]
Please mark brainly if it helped you out!~
Answer: 245
Step-by-step explanation:
first you have to 7 for the square which = 14
then after that you do 1/2 b x h = 1/2 7 x 14= 3.5 x 14= 49 but then you have 4 triangles so 49 x 4=196. Then 49 + 196= 245
Classify the system of equations. 3x = -2- y 4+ y = -3x+1 Click on the correct answer. intersecting parallel coincident
Step-by-step explanation:
rearrange the equations first
y=-3x-2---eq(1)
y=-3x+1-4
y=-3x-3---eq(2)
In first eq slope is -3x and y-intercept is -2
In second equation, the slope is -3x and y-intercept is -3
the slopes are the same in both equations but the y-intercepts are different
so the lines are parallel. The system is inconsistent
For this case we have the following system of equations:
[tex]3x = -2-y\\4 + y = -3x + 1[/tex]
By clearing "y" from both equations we have:
Equation 1:
[tex]3x + 2 = -y\\y = -3x-2[/tex]
Equation 2:
[tex]y = -3x + 1-4\\y = -3x-3[/tex]
It is observed that the slopes of both equations are equal. Recall that the equation of a line in the slope-intersection form is given by:
[tex]y = mx + b[/tex]
Where "m" is the slope.
If the slopes are equal, then the lines are parallel.
Answer:
Parallel
Solve this radical equation (square root of x+11)-x=-1
[tex]\bf \sqrt{x+11}-x=-1\implies \sqrt{x+11}=x-1\implies \stackrel{\textit{squaring both sides}}{(\sqrt{x+11})^2=(x-1)^2} \\\\\\ x+11=\stackrel{\mathbb{F~O~I~L}}{x^2-2x+1}\implies 11=x^2-3x+1\implies 0=x^2-3x-10 \\\\\\ 0=(x-5)(x+2)\implies x= \begin{cases} 5\\ -2 \end{cases}[/tex]
Gives x = -5 or x = 2.
Learn how to solve radical equations step by step by isolating terms and squaring, resulting in solutions to the given equation.
To solve the equation (square root of x+11)-x=-1, follow these steps:
Isolate the square root term: square root of x+11=-1+xSquare both sides to eliminate the square root: x+11 = x^2+2x+1Rearrange the equation and solve the quadratic: x^2+x-10=0, which gives x = -5 or x = 2
if f(x) = 3x - 2 and g(x) = 2x + 1, find (f - g)(x)
Answer:
(f-g)(x) = x-3
Step-by-step explanation:
Given
f(x) = 3x-2
and
g(x) = 2x+1
We have to find (f-g)(x)
So,
(f-g)(x) = f(x)-g(x)
= 3x-2 - (2x+1)
= 3x-2-2x-1
=x-3
Hence,
(f-g)(x) = x-3
Answer:
( f - g ) ( x ) = x - 3
Step-by-step explanation:
We are to find [tex] ( f - g ) ( x ) [/tex] given that [tex] f ( x ) = 3 x - 2 [/tex] and [tex] g ( x ) = 2 x + 1 [/tex].
So basically we have to subtract the function g from function f.
[tex] ( f - g ) ( x ) = f(x) - g(x) [/tex]
Substituting the given functions in the above equation to get:
[tex] ( f - g ) ( x ) = (3x - 2) - (2 x + 1 ) [/tex]
[tex] ( f - g ) ( x ) = 3x - 2 - 2 x - 1 [/tex]
[tex] ( f - g ) ( x ) = 3x - 2 x - 2 - 1 [/tex]
[tex] ( f - g ) ( x ) = x - 3 [/tex]
Inverse of f(x)=3x-4
Answer:
[tex]\large\boxed{f^{-1}(x)=\dfrac{x+4}{3}=\dfrac{1}{3}x+\dfrac{4}{3}}[/tex]
Step-by-step explanation:
[tex]f(x)=3x-4\to y=3x-4\\\\\text{exchange x to y and vice versa}\\\\x=3y-4\\\\\text{solve for y}\\\\3y-4=x\qquad\text{add 4 to both sides}\\\\3y=x+4\qquad\text{divide both sides by 3}\\\\y=\dfrac{x+4}{3}[/tex]
❤️❤️☺️Hello MATHS Experts☺️❤️❤️, Solve This Problem Please
Answer:
x = 70°y = 55°z = 55°Step-by-step explanation:
Look at the picture.
We know: the sum of the angles measure in the triangle is 180°. Therefore we have the equation:
[tex]35^o+35^o+\alpha=180^o[/tex]
Solve it:
[tex]70^o+\alpha=180^o\qquad\text{subtract}\ 70^o\ \text{from both sides}\\\\\alpha=110^o[/tex]
Angle α and β = x are the supplementary angles. Supplementary angles add up to 180°. Therefore:
[tex]\alpha+\beta=180^o[/tex]
[tex]110^o+\beta=180^o\qquad\text{subtract}\ 110^o\ \text{from both sides}\\\\\beta=70^o[/tex]
[tex]\beta+\gamma+\gamma=180^o[/tex]
[tex]70^o+2\gamma=180^o\qquad\text{subtract}\ 70^o\ \text{from both sides}\\\\2\gamma=110^o\qquad\text{divide both sides by 2}\\\\\gamma=55^o[/tex]
Help me on this math question
Answer: B. 36
Step-by-step explanation: Round each number.
11.72 -> 12
3.01 -> 3
Multiply the rounded numbers.
12 x 3 = 36
The answer would be 36.
Factor this expression.
4x - 16
Hii!
__________________________________________________________
Answer:
Step-by-step explanation:
Note that both terms, 4x and -16, have something in common.
In math, this "something" is known as the greatest common factor (g.c.f.).
The g.c.f. of 4x and -16 is 4, so that's what we factor out.
First, we divide both 4x and -16 by 4.
We obtain.
x-4
Put parentheses around x-4
(x-4)
Now put 4 outside the parentheses
4(x-4)
--
Hope that this helped! Best wishes,
--
The factored form of the expression 4x - 16 is 4(x - 4).
To factor the expression 4x - 16, we can look for the greatest common factor (GCF) of the terms. In this case, both terms have a common factor of 4.
We can factor out the GCF of 4 from each term:
4x - 16 = 4(x - 4)
Therefore, the factored form of the expression 4x - 16 is 4(x - 4).
Learn more about factored form here:https://brainly.com/question/25094938
#SPJ2
Type the correct answer in each box.
The value of x is °, and the value of y is
°.
Answer:
x = 60°, y = 50°Step-by-step explanation:
We know: the angles measures in a triangle add up to 180°.
(look at the picture)
z + 50 + 60 = 180
z + 110 = 180 subtract 110 from both sides
z = 70°
x + 50 + 70 = 180
x + 120 = 180 subtract 120 from both sides
x = 60°
Angles x, y and z are on one side of a straight line. Therefore they add to 180°.
x + y + z = 180
60 + y + 70 = 180
y + 130 = 180 subtract 130 from both sides
y = 50°
Answer:
x = 60°, y = 50°
Step-by-step explanation:
We know: the angles measures in a triangle add up to 180°.
z + 50 + 60 = 180
z + 110 = 180 subtract 110 from both sides
z = 70°
x + 50 + 70 = 180
x + 120 = 180 subtract 120 from both sides
x = 60°
Angles x, y and z are on one side of a straight line. Therefore they add to 180°.
x + y + z = 180
60 + y + 70 = 180
y + 130 = 180 subtract 130 from both sides
y = 50°
Oscar gained x pounds within the last year. he weighed 96 pounds last year. which expressions correctly describes his current weight?
a. 96 - x
b. 96 + x
c. 96x
d. 96/x
Answer:
b
becasue to find his current weight you would use what you know and the amount of lbs he added (represented as x)
96 + x
Step-by-step explanation:
What is the solution to the equation x over 3 + x over 6 = 7 over 2
Answer:
x=7
Step-by-step explanation:
The given equation is:
[tex]\frac{x}{3}+\frac{x}{6} = \frac{7}{2}[/tex]
Multiplying both sides by LCM of 3 and 6
So,
[tex]\frac{x}{3}*6+\frac{x}{6}*6 = \frac{7}{2}*6\\2x+x=7*3\\3x=21\\\frac{3x}{3} =\frac{2}{3}\\ x=7[/tex]
Hence, the solution of the equation is x=7 ..
Answer: x = 7
Step-by-step explanation:
(x/3)+(x/6)=7/2
add variables
(2x+x)/6=7/2
combine like terms
3x/6=7/2
simplify
x/2=7/2
multiply denominators by 2
x=7
Osvoldo has a goal of getting at least 30%, percent of his grams of carbohydrates each day from whole grains. Today, he ate 220 grams of carbohydrates, and 55grams were from whole grains.
Did Osvoldo meet his goal? How many grams of whole grain did he eat?
Answer:
Osvoldo does not meet his goal
He had to have eaten at least 66 grams of whole grains to meet his goal.
Step-by-step explanation:
step 1
Find out the 30% of the grams of carbohydrates that Osvoldo ate today
Remember that
30%=30/100=0.30
so
0.30(220)=66 grams
step 2
Compare the 30% of the grams of carbohydrates that Osvoldo ate today with the 55 grams of whole grains
we know that
To Osvoldo meet his goal the 55 grams of whole grain must be greater than or equal to the 30% of the grams of carbohydrates that Osvoldo ate today
55 < 66
therefore
Osvoldo does not meet his goal
He had to have eaten at least 66 grams of whole grains to meet his goal.
Which of the following best describes the locust of points equidistant from a given directrix and focus?
A. Parabola
B. Circle
C. Ellipse
D. Hyperbola
Answer:
A. Parabola
Step-by-step explanation:
Parabola best describes the locust of points equidistant from a given directrix and focus.
Parabola is the curve that best describes the locus of points equidistant from a given directrix and focus. This can be obtained by understanding what a parabola is.
What is a parabola?Parabola is a locus of points equidistant from a given fixed point and fixed line.The fixed point is focus and the fixed line is directrix.Standard equation of a parabola:The equation is y² = 4ax, when directrix is parallel to the y-axis, a is distance from origin to focus.
Hence parabola is the curve that best describes the locus of points equidistant from a given directrix and focus.
Learn more about parabola here:
brainly.com/question/4074088
#SPJ2
Graph the equation y=1/2x+5 on the coordinate plane provided below / PLS HELP!
Answer:
Step-by-step explanation:
Y/1 = 2x + 5
Y = 2x + 5
Y = 2x + 5
When x = 1
Y = 2 ×1 +5
Y = 2 + 5
Y = 7
When x =0
Y = 2 × 0 + 5
Y = 5
When x = -2
X = 2 × -2 + 5
X = 1
( Make a table in the side of the page)
X | 1 0 -2
_ _______
Y 7 5 1
The graph for the coordinate points (0, 5), (1, 5.5), (2, 6), (3, 6.5) and (4, 7) is plotted below.
What is the equation of a line?The general equation of a straight line is y=mx+c, where m is the gradient, and y = c is the value where the line cuts the y-axis. This number c is called the intercept on the y-axis.
The given equation of a line is y=1/2x+5.
Substitute x=0, 1, 2, 3, 4, 5,....in a equation y=1/2x+5, we get
When x=0, y=5
When x=1, y=5.5
When x=2, y=6
When x=3, y=6.5
When x=4, y=7
So, the coordinate points are (0, 5), (1, 5.5), (2, 6), (3, 6.5) and (4, 7)
Therefore, the graph for the coordinate points (0, 5), (1, 5.5), (2, 6), (3, 6.5) and (4, 7) is plotted below.
To learn more about the equation of a line visit:
https://brainly.com/question/2564656.
#SPJ5
What is the measure of angle E, in degrees?
The answer is 84 degrees because d and f both are 48 degrees so that adds up to 96. So that means you add 84 plus 96 which is 180 so the answer is 84 degrees.
Answer. The answer is 84
What is the greatest common factor of the polynomial 40x^7+135x^4+5x^4
5x^4
Step-by-step explanation:
simply we take 5x^4 bec. it can be divided by 40 and 135
Choose the correct product of (6x + 2)2.
Answer:
36x² + 24x + 4
Step-by-step explanation:
Given
(6x + 2)² = (6x + 2)(6x + 2)
Each term in the second factor is multiplied by each term in the first factor, that is
6x(6x + 2) + 2(6x + 2) ← distribute both parenthesis
= 36x² + 12x + 12x + 4 ← collect like terms
= 36x² + 24x + 4
please answer this.
Also if you can, please answer my other question its very simmilar
For this case we have that a percentage equivalent to[tex]\frac {1} {8}[/tex]is given by:
[tex]x = \frac {1} {8} * 100 =[/tex] 12.5%
Then, according to the steps, it is observed that Harriet made an incorrect division, deboa multiply. So, the second step is the wrong one.
Answer:
Option B
if f(x)=(x+3)³+4
let g(x)=f(x+1)-2
find when g(x)=12
Answer:
[tex]x=\sqrt[3]{10}-2[/tex]
Step-by-step explanation:
The composite function (f(x+1)) is moved in the x-axis by -1, you know this by solving x+1=0.
The equivalent expresion for f(x+1) is
[tex]f(x+1)= (x-1+3)^{3}+4[/tex]
[tex]f(x+1)=(x+2)^{3}+ 4[/tex]
Eval the above expression in g(x)
[tex]g(x)=(x+2)^{3}+4-2[/tex]
We must find x that gives g(x)=12
The equation is the following
[tex]12=(x+2)^{3}+2[/tex]
Grouping terms>
[tex](x+2)^{3} =10[/tex]
To solve for x, must apply cubic root in both sides of equation:
[tex]\sqrt[3]{(x+2)^{3} } =\sqrt[3]{10}[/tex]
it then turns in the following>
[tex]x+2=\sqrt[3]{10}\\[/tex]
Giving the stated answer
mk
---, for m = 6 and k = 2
m+k
So you're asking to evaluate this equation?
mk/m+k for m = 6 and k = 2
what are the domain and range of the absolute value parent function
Answer:
C. The domain is all real numbers, and the range is non-negative real numbers( [tex]y\ge0[/tex])
Step-by-step explanation:
The absolute value parent function is [tex]y=|x|[/tex]
The domain of a function refers to all values of x for which the function is defined.
The parent absolute value function is defined for all values of x.
Therefore the domain is all real numbers.
The range refers to the y-values for which x is defined.
The parent has a v-shape and its vertex is at the origin.
Therefore the least y-value is 0 and there is no maximum y-value.
The range is [tex]y\ge0[/tex]
See attachment.
You deposit $5000 in an account earning 8% interest compounded monthly. How much will you have in the account in 15 years?
[tex]\bf ~~~~~~ \textit{Compound Interest Earned Amount} \\\\ A=P\left(1+\frac{r}{n}\right)^{nt} \quad \begin{cases} A=\textit{accumulated amount}\\ P=\textit{original amount deposited}\dotfill &\$5000\\ r=rate\to 8\%\to \frac{8}{100}\dotfill &0.08\\ n= \begin{array}{llll} \textit{times it compounds per year}\\ \textit{monthly, thus twelve} \end{array}\dotfill &12\\ t=years\dotfill &15 \end{cases}[/tex]
[tex]\bf A=5000\left(1+\frac{0.08}{12}\right)^{12\cdot 15}\implies A=5000(1.00\overline{66})^{180}\implies A\approx 16534.61[/tex]
6. Identify which of the following are sets.
I: The collection of all the days in a week.
II: The collection of all teachers in a school.
III: The collection of all integers more than -5.
A. I only
B.I, II
C.III only
D. I, II, III
Answer:
D. I, II, III
Step-by-step explanation:
Let us look at the definition of set:
A set is a collection of well-defined and distinct objects
I: The collection of all the days in a week.
The set will consist of seven elements.
II: The collection of all teachers in a school.
Also a set.
III: The collection of all integers more than -5.
This is a set.
Therefore, Option D is correct ..
Lela purchased three mechanical pencils and a notebook that cost five dollars per purchase totaled $11 how much was each pencil use P to represent the cost of each pencil
Answer: 3p+5=11
Step-by-step explanation:
3p+5=11
-5 -5
3p=6
3p/3=6/3
P=2
$2
The cost of each pencil is $2.
What is a word problem?A word problem is a verbal description of a problem situation. It consists of few sentences describing a 'real-life' scenario where a problem needs to be solved by way of a mathematical calculation.
For the given situation,
Number of pencils = 3
Number of notebook = 1
Cost of a notebook = $5
Total cost = $11
Let number of pencil be p.
Lela purchased three mechanical pencils and a notebook is
⇒ [tex]3p+5=11[/tex]
⇒ [tex]3p=11-5[/tex]
⇒ [tex]3p=6[/tex]
⇒ [tex]p=\frac{6}{3}[/tex]
⇒ [tex]p=2[/tex]
Hence we can conclude that the cost of each pencil is $2.
Learn more about word problems here
brainly.com/question/20594903
#SPJ2
20 Points 20 points 20 points
Answer:
-5Step-by-step explanation:
[tex]A=\left[\begin{array}{ccc}a&b\\c&d\end{array}\right] \\\\\det A=\left|\begin{array}{ccc}a&b\\c&d\end{array}\right|=ad-bc[/tex]
[tex]\left\{\begin{array}{ccc}x+2y=5\\x-3y=7\end{array}\right\\\\A=\left[\begin{array}{ccc}1&2\\1&-3\end{array}\right] \\\\\det A=A=\left|\begin{array}{ccc}1&2\\1&-3\end{array}\right|=(1)(-3)-(1)(2)=-3-2=-5[/tex]
Answer:
-5
Step-by-step explanation:
can any number of lines pass through two given points
[tex]\huge{\boxed{\text{No.}}}[/tex]
Unless the points are both the same point, there is only one straight line to connect them both. Any other line would either only touch one point or touch neither of the points.
what is the midpoint of the verticle line segment graphed below?
Answer:
C (2, -5/2)
Step-by-step explanation:
To find the midpoint of two points
mid = (x1+x2)/2, (y1+y2)/2
= (2+2)/2, (4+-9)/2
= 4/2, -5/2
=2,-5/2